Redefining Economic Policy and Institutional Reform – Support for Economic Growth - Coralia ANGELESCU; Laurenţiu DINU (Theoretical and Applied Economics, 2010)
The paper addresses the effects of economic crisis fromthe perspective of theoretical developments and how they were reflectedin the economy, both nationally and among the actors of the internationalsystem. Basic economic paradigms such as the role of price as amechanism regulating the operation of free markets and the ability todetermine prices to reflect economic developments have been tested invarious markets. In the context of limited resources available, due toeconomic contraction it is necessary to redefine accepted socialbalances.The example analyzed in the paper is that of social policies. Intimes of economic expansion, modification of such arrangements, even ifsuboptimal, proves to be difficult because it involves implicit costs, lessvisible. Economic crisis brings out such costs. Changing these socialarrangements requires first the solution and coherent regulatorymechanisms and implementation. They depend on the quality ofinstitutions and social coordination system as a whole. If thesemechanisms are complex national, at supranational level we can addadditional layers of decision, which explains the difficulty of coordination. The degree of consistency in decision-making mechanismsand their quality determine the cost of adapting to new conditionsimposed by the balance.Coordination mechanisms, either national or supranationalcontext, are relevant for redefining of a new balance to streamlineexisting policies (eg social) that reflects the crisis and the creation of newarrangements to accommodate new engines economic growth.